2010
DOI: 10.29333/ejgm/82897
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Nasopharyngeal Angiofibroma

Abstract: Review of the literature was performed to define the optimal treatment of patients with juvenile nasopharyngeal angiofibroma (JNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 22 publications
0
33
0
6
Order By: Relevance
“…The mass is well defined, non-encapsulated and lobulated with epicenter around sphenopalatine foramina. There is intense enhancement seen because of the high vascular contents [6,7]. There is resorption or remodeling of the bone rather than the destruction which makes it different from aggressive and malignant pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The mass is well defined, non-encapsulated and lobulated with epicenter around sphenopalatine foramina. There is intense enhancement seen because of the high vascular contents [6,7]. There is resorption or remodeling of the bone rather than the destruction which makes it different from aggressive and malignant pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of muscle, elastic fibers is the cause for massive hemorrhage even with slight manipulation at the tumor site. 5 Patients typically present with progressive nasal obstruction (80-90%), recurrent epistaxis (40%), swelling of the cheek as seen in this case report. Headache and facial pain may arise due to involvement of para nasal sinuses.…”
Section: Discussionmentioning
confidence: 87%
“…Radiation may lead to complications such as growth retardation, temporal lobe radionecrosis, keratopathy and potential carcinogenic side-effects. 6,12,13 Chemotherapy is not very effective. 6 As JNA growth is androgen-dependent, antiandrogen therapy decreases the size and vascularity of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 There have been conflicting recommendations in different studies with regard to flutamide, an androgen receptor blocker, which has been found to have unproven efficacy. However, it is of particular interest in partial volume reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation